Effect of a novel endoscope cleaning brush on duodenoscope contamination - van der Ploeg, Koen; Haanappel, Cynthia P.; Voor in ’t holt, Anne F.; de Groot, Woutrinus; Bulkmans, Adriana J.C.; Erler, Nicole S.; Mason-Slingerland, Bibi C.G.C.; Vos, Margreet C.; Bruno, Marco J.; Severin, Juliëtte A. (Endoscopy, 2023)
Background Current duodenoscope reprocessing protocols are insufficient to prevent contamination and require adaptations to prevent endoscopy-associated infections (EAIs). This study aimed to investigate the effect of a new endoscope cleaning brush on the contamination rate of ready-to-use duodenoscopes.Methods This retrospective before-and-after intervention study collected duodenoscope surveillance culture results from March 2018 to June 2022. Contamination was defined as ≥1 colony-forming unit of a microorganism of gut or oral origin (MGO). In December 2020, an endoscope cleaning brush with a sweeper design was introduced as an intervention in the manual cleaning of duodenoscopes. A logistic mixed-effects model was used to study the effects of this intervention. Results Data were collected from 176 culture sets before the new brush’s introduction and 81 culture sets afterwards. Pre-introduction, culture sets positive with an MGO comprised 45.5% (95%CI 38.3%–52.8%; 80/176), decreasing to 17.3% (95%CI 10.6%–26.9%; 14/81) after implementation of the new brush. Compared with the former brush, duodenoscopes cleaned with the new brush had lower odds of contamination with MGOs (adjusted odds ratio 0.25, 95%CI 0.11–0.58; P=0.001)Conclusions Use of the new brush in manual cleaning reduced contamination with MGOs and is expected to prevent EAIs. These findings should be confirmed in future prospective randomized studies.